Unsteady Mixed Convection Flow in the Stagnation Region of a Three Dimensional Body Embedded in a Porous Medium - Ibrahim, F. S. S. (Nonlinear Analysis: Modelling and Control, 2008)
An analysis is preformed to study the heat transfer characteristic of unsteady mixed convection flow of a viscous fluid in the vicinity of a stagnation point of a general three-dimensional body embedded in a porous media. The velocity in the potential flow is assumed to vary arbitrary with time. The non-Darcy effects including convective, boundary and inertial effects are included in the analysis. Both nodal-point region (0 ≤ c ≤ 1), where c = b/a is the ratio of the velocity gradients in y and x directions in the potential flow and saddle point region (−1 ≤ c < 0) are considered. The semisimilar solutions of the momentum and energy equations are obtained numerically using finite difference method. Also a self-similar solution is found when the velocity in the potential flow and the wall temperature vary with time in particular manner. Many results are obtained and a representative set is displayed graphically to illustrate the influence of the physical parameters on the surface shear stresses and the surface heat transfer.
Keywords: unsteady flow; mixed convection; stagnation-point; self-similar solution; porous media